The purpose of life - Lang, Jeffrey; One Islam Productions; Mecca Centric Da'wah Group (N.S.W, Australia : One Islam Productions, 2006)
From an atheist to Muslim, Jeffrey Lang shares his experience of the world as a young man struggling to find meaning in a life full of crisis. He details his experience of growing up in the suburbs of San Francisco and how his reading of the Holy Quran changed his worldview entirely. He explains how within Quran, he found all the answers to his philosophical questions such as why evil exists in the world, who is God, and what is the purpose of life
Title from title screen
One of the workpaper presents in The 2nd Annual Iowa Conference on Islam, Ames, Iowa, March 29th-31st 2002
Presenter : Jeffrey Lang
Keywords: Islam -- Customs and practices; Religious life -- Islam